Teaching Semiotics to Promote Studentsâ Critical Thinking in the Reading and Writing Class - Priadi, Arum (Sebelas Maret University, 2016)
This study aims at stimulating studentsâ criticism when reading and writing. Reading should not be passive since it needs critical thinking to understand the text. What is presented in the text describes a discourse; therefore, the students should communicate with the text to get the points. The discourse relates to context and a text is a media to cover. As the media of the discourse, text encourages students to think critically in order that they can give some comments and inputs after reading. The comments and inputs, then, are manifested in writing so it shows a complex activity which contains studentsâ comprehension. In other words, writing becomes an indicator to evaluate the result of the reading activities which have been completed before. Semiotics is one important thing. It presents signs and symbols providing certain meanings both explicitly and implicitly. Students create their interpretations with different views which is based on what they think. Critical thinking takes its role in observing the signs and symbols distributed elsewhere in the text. The process of making interpretation is a way to communicate with the text because they are certainly engaged when exploring ideas and connecting among information then developing into a written form. This study takes the students of Pre Advanced Reading and Writing in the third year of Ahmad Dahlan University, Yogyakarta.